Doctor Zhivago - Pasternak, Boris Loenidovic, 1890-1960 (Collins and Harvill Press, 1958)
Doctor Zhivago is a sweeping epic romantic novel set during pre- revolutionary times in Russia and leading the main characters through WWI and the Russian Revolution of 1917. The main characters involoved inthis love traingle represent different facets of Russia before and during the countries transformation from a monarchical society to a communist society. The two main themes involve the idea of a free personality embodied in the character of Lara vs. the strong atheistic personality seen in her husband Pasha Anitpov. Doctor Zhivago represents the poetic soul of Mother Russia, free from political ideology who desires to live and love and be free to choose.